ANALYSIS OF MANTRA RITUAL STRUCTURE REJECT REVOLUTION THE COMMUNITY OF MELAYU IN PANTAI LABU DISTRICT DELI SERDANG DISTRICT NORTH SUMATRA - Tiflatul Husna; Putri Juwita; Budiman Budiman (SENSEI RESEARCH CENTER, 2021)
Mantra is a part of oral literature that has been passed down into culture. Its presence has colored the world of Indonesian literature. From there, the development of literature began. As part of literature, spells have their own uniqueness. The author is anonymous, the contents in it are interwoven words that collect magical power. Likewise, the ritual mantra of rejecting reinforcements in this case is the antidote for headaches that exist in the association of the Malay community in Pantai Labu District, Deli Serdang Regency, North Sumatra. Based on the background, the problems examined in this study are (1) how is the physical structure of the ritual mantra to repel headaches and (2) how is the inner structure of the ritual of repelling headaches. This research is descriptive qualitative. By reading the spell text and analyzing it. Based on the results of data analysis, it can be concluded that there are two physical structures with diction, namely medang and meranti wood, the image used is a visual image, namely the word growing in the field there, nodding, tapping, concrete words twice and in the form of repetition of figures. Meanwhile, rhyme is only found in one line 2 and 3 with a two-stanza typography consisting of 6 lines of verse 1 and 8 lines of stanza 2. In the study of the inner structure, the theme of hope for healing from God presents a feeling that God loves and loves so that the tone is accepted by the reader is surrender and tawakal. So, the mandate that can be taken from this mantra is expressly submission to Allah. What is done with a mantra is only as a form of effort.